Causes of under-five mortality using verbal autopsy and social autopsy studies (VASA) in Alexandria, Egypt, 2019 - Ramy Mohamed Ghazy; Mohga M Fekry; Abdel-Rahman Omran; Mohamed Mostafa Tahoun (Journal of Global Health Reports)
# Background